If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6f=-60
We move all terms to the left:
6f-(-60)=0
We add all the numbers together, and all the variables
6f+60=0
We move all terms containing f to the left, all other terms to the right
6f=-60
f=-60/6
f=-10
| 6v-9=19 | | b+3b=24 | | 84=6e | | 10.79=u+2 | | 23.7-y=10 | | 1-j=3 | | -88=-10=6k | | 3+c=-4 | | 3y–12=-2y-12 | | 6x+27=-60 | | (5x^2)+13=0 | | 8.97=3n | | 110=-35x+40 | | -12.5+m=17.5 | | 8f+21=-7f-19 | | 5x=60=40 | | 4/k=14 | | 6.93+a=6.97 | | 12x–(4x+10)=54 | | 23.7–yy=10 | | k/4+ –16=–17 | | 4^(3x+1)=3^(2x-3) | | 2x-10=3x+28 | | j/2.13=4 | | 4x+10=5x-8=3x+1 | | 46-u=228 | | -15(x-1)=40 | | 1+18x=33 | | 23.7–y=10 | | 15(x-1)=40 | | c+8.32=15.97 | | 37=-y/5 |